THE NOTION OF GENRE WITHIN THE FIELD OF LITERARY ANALYSIS - Rustamov Ilkhom Tursunovich; Mardanova Nafisa Tursunovna (Journal of new century innovations, 2024)
Abstract: This article explores the notion of genre in the context of literary analysis. Genres act as essential structures for comprehending and classifying literary pieces, offering readers and scholars valuable perspectives on a text's organization, themes, and stylistic elements. By investigating diverse literary genres and their defining traits, this research seeks to clarify the importance of genre in the interpretation and enjoyment of literature.